2018
DOI: 10.1111/obr.12763
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to increase physical activity in children 0–5 years old: a systematic review, meta‐analysis and realist synthesis

Abstract: Summary Objective The objective of the study is to evaluate the effectiveness of interventions to increase physical activity (PA) in 0–5 year olds and to determine what works, for whom, in what circumstances. Design Systematic review, meta‐analysis and realist synthesis. Data sources Embase and EBSCOhost (Academic Search Complete, CINAHL Complete, Global Health, MEDLINE Complete, PsycINFO, SPORTDiscus with full text), up to and including April 2017. Eligibility criteria Published in a peer‐reviewed English lan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
75
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(83 citation statements)
references
References 80 publications
(155 reference statements)
7
75
0
1
Order By: Relevance
“…These include cluster analysis, based on either geometric (e.g., k-means) or probabilistic (e.g., mixture models) methods, they are aimed at grouping observations into homogeneous clusters [9]. This approach is attractive in part because of its potential practical value, understanding which obesogenic behaviors need to be targeted together and in whom can provide us with useful information for tailoring interventions to the needs of specific groups at higher risk [6,10], and thereby increasing the effectiveness of existing pediatric obesity prevention strategies [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…These include cluster analysis, based on either geometric (e.g., k-means) or probabilistic (e.g., mixture models) methods, they are aimed at grouping observations into homogeneous clusters [9]. This approach is attractive in part because of its potential practical value, understanding which obesogenic behaviors need to be targeted together and in whom can provide us with useful information for tailoring interventions to the needs of specific groups at higher risk [6,10], and thereby increasing the effectiveness of existing pediatric obesity prevention strategies [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…These results support the notion that the early learning environment is an ideal setting to facilitate MVPA in preschoolers. A more recent review also reported a small but positive effect of childcare center interventions in increasing physical activity in young children [26]. Furthermore, these authors highlight the importance of outdoor play in increasing children's physical activity levels.…”
Section: Introductionmentioning
confidence: 89%
“…What is not clear throughout the literature is if interventions aimed at improving FMS would confer a greater advantage over interventions that are specifically aimed at increasing physical activity levels directly. Furthermore, although both FMS [13] and physical activity [26] interventions have shown different effects for biological sex, no effort has been made to determine which type of intervention would be most beneficial for girls who consistently demonstrate lower physical activity and ball skills compared to their male counterparts. Finally, it is not clear how interventions should be tailored to benefit all children regardless of age, sex, and current level of physical activity, all of which have been postulated to influence physical activity outcomes [26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Childhood obesity has become a primary focus of Head Start programs (federally funded preschool programs for low-income families) (Early Childhood Learning and Knowledge Center, 2018). As preschool/childcare interventions can lead to increases in MVPA (Hnatiuk et al 2019), preschools have implemented different strategies to increase PA and prevent obesity in their attendees. These strategies have included implementing PA curricula aimed at improving fundamental movement skills (Zahnd et al 2017), engaging families by providing materials for PA and hosting family events (Davis et al, 2013), empowering parents to become involved with their children's PA (Keeney, Schneider, & Carter, 2016), and including parents in the intervention design (Davison, Jurkowski, Li, Kranz, & Lawson, 2013).…”
Section: Introductionmentioning
confidence: 99%